2006
DOI: 10.1002/joc.1394
|View full text |Cite
|
Sign up to set email alerts
|

Indian summer monsoon rainfall and its link with ENSO and Indian Ocean climate indices

Abstract: Abstract:We examine the relationship between the state of the equatorial Indian Ocean, ENSO, and the Indian summer monsoon rainfall using data from 1881 to 1998. The zonal wind anomalies and SST anomaly gradient over the equatorial Indian Ocean are used as indices that represent the condition of the Indian Ocean. Although the index defined by the zonal wind anomalies correlates poorly with Indian summer monsoon rainfall, the linear reconstruction of Indian summer monsoon rainfall on the basis of a multiple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 25 publications
6
83
0
Order By: Relevance
“…A monthly index of zonal surface wind for the equatorial Indian Ocean (EQWIN) is based on ICOADS data for anomalies averaged over 62°-90°E, 4°N-4°S, for 1884-1997 (Worley et al, 2005). EQWIN is a sensitive indicator of Indian Ocean climate which has been utilized to improve a simple predictive model of the Indian monsoon based on Niño-3 SST, while the DMI did not show a strong relationship (Gadgil et al, 2004;Ihara et al, 2007). Rainfall data were obtained from the GPCC Variability Analysis of Surface Climate Observations (Beck et al, 2005, Vasclim-0 0.5, 1951-2000 precipitation data set.…”
Section: Methodsmentioning
confidence: 99%
“…A monthly index of zonal surface wind for the equatorial Indian Ocean (EQWIN) is based on ICOADS data for anomalies averaged over 62°-90°E, 4°N-4°S, for 1884-1997 (Worley et al, 2005). EQWIN is a sensitive indicator of Indian Ocean climate which has been utilized to improve a simple predictive model of the Indian monsoon based on Niño-3 SST, while the DMI did not show a strong relationship (Gadgil et al, 2004;Ihara et al, 2007). Rainfall data were obtained from the GPCC Variability Analysis of Surface Climate Observations (Beck et al, 2005, Vasclim-0 0.5, 1951-2000 precipitation data set.…”
Section: Methodsmentioning
confidence: 99%
“…Gadgil et al ( , 2004 showed that there is a strong relationship between the extremes (droughts and excess monsoon seasons) and a composite index which is a linear combination of the ENSO index and EQWIN. Using a longer dataset (from 1881 to 1998), Ihara et al (2007) showed that the variation of ISMR is better described by the use of indices of ENSO as well as EQWIN than by ENSO index alone. The inference of Krishnamurthy and Shukla (2008) on the importance of these two modes for interannual variation of the monsoon is consistent with these studies demonstrating the importance of ENSO and EQUINOO.…”
Section: Intraseasonal and Interannual Variations Of Ismrmentioning
confidence: 97%
“…El Niño events (warmer than normal sea surface temperature (SST) in the eastern equatorial Pacific) are linked to a deficit in the all-India summer monsoon rainfall (Ihara et al, 2007 and see references therein). However, El Niño's influence on the monsoon is not always proportional to its strength.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies propose that the Indian Ocean Dipole (IOD) mode (Saji et al, 1999;Webster et al, 1999) and the related phenomena explain unusual monsoon behaviour during El Niño (Ashok et al, 2001(Ashok et al, , 2004Gadgil et al, 2003Gadgil et al, , 2004Ihara et al, 2007). Ihara et al (2007) discussed an association between climate anomalies over the Indian Ocean, summer monsoon rainfall and El Niño, however, they did not find a statistically significant association between the all-India summer monsoon rainfall, area-weighted averaged total rainfall of the summer monsoon season obtained from the raingauge stations over entire India, and the June-September IOD-mode index based on SST anomalies from 1881 to 1998. In general, it is known that some parts of the Indian Ocean SSTs are influenced by both ENSO (Klein et al, 1999 and many others) and the monsoon circulation (Shukla, 1987).…”
Section: Introductionmentioning
confidence: 99%